Time to Lupus Low Disease Activity State in the Hopkins Lupus Cohort: Role of African-American Ethnicity. - Babaoglu, Hakan (Arthritis Care Res (Hoboken), 2020)
BACKGROUND: Lupus Low Disease Activity State (LLDAS) is a potential treat to target goal in systemic lupus erythematosus (SLE). This study determined predictors of time to reach LLDAS in a longitudinal cohort. METHODS: Patients were grouped according to LLDAS status at cohort entry. Those who did not satisfy LLDAS at cohort entry were analyzed prospectively. The Kaplan Meier approach was used to estimate the time to LLDAS. Cox regression was used to identify patient characteristics that were associated with time to LLDAS. RESULTS: The probability of LLDAS attainment within one year was 52% for Caucasians, 36% for African-Americans and 33% for SLE patients with renal involvement. The median time to LLDAS was 1.1 years. In multivariable models, African-American ethnicity, baseline prednisone >10 mg daily, hypocomplementemia, baseline damage, and baseline renal activity remained significant predictors of longer time to attain LLDAS, while disease duration <1 year and cutaneous activity were associated with earlier attainment. CONCLUSIONS: LLDAS is potentially attainable in the majority of SLE patients. The time to LLDAS was found to be longer in African-American SLE patients. Characteristics of African-American SLE patients such as renal activity and hypocomplementemia were also independent predictors of slower attainment of LLDAS. These findings point to the need to include African-American SLE patients in both clinical and pharmaceutical research.